Nursing diagnoses of the domains self-perception and coping/tolerance of stress related to female infertility - Andressa Carioca Bezerra; Viviane Martins da Silva; Paula Sacha Frota Nogueira; Raquel de Serpa Torres Martins; Rebeca Pinho Romero Vieira; Sarah Maria Fraxe Pessoa (Universidade Federal de Goias, 2016)
The objective was to characterize the profile of nursing diagnoses of the domains Self-perception and Coping/Tolerance of stress of women with infertility complaints. A descriptive, quantitative study conducted with 40 women, in a primary health care unit. Data was collected with an interview form created for this study. We identified 20 diagnoses. Improved readiness for power, Improved readiness for coping, Improved readiness for resilience, Anxiety and, Low situational self-esteem presented were more frequent. The findings revealed that infertility can generate anxiety and negatively affect women's self-perception. However, this clientele demonstrated readiness to optimize their wellbeing. Identification of diagnoses contributes with care planning and enriches the quality of assistance, allowing women to be prepared for achieving maternity or not, through individualized nursing interventions, including emotional and psychosocial support according to the need of each one of them.